О благоустройстве сельских поселений на территории Херсонесской хоры (по материалам поселения Маслины) - Латышева, В. А. (Давнина. Харківський історико-археологічний щорічник, 2016)
SUMMARY Latysheva V.A. On the Improvement of Rural Settlements on the Territory of Chersonesus Chora (on the materials of settlement Masliny) The analysis of the materials of the settlement Maslini lets to conclude that the degree life conveniencies was various on the territory of Khersonesus khora: there is a representative house like a tower, with the high level of the building, qualitative inner decoration, a set of the expensive imported things, good system of the water-supply, specially equipped bathroom etc., and there are dugouts and half-dugouts with theminimum of the elementary conveniencies and common everyday things. The first one belonged to the representatives of the rather high social rank, the second — to the average or dependent population.